Digital Dharma : Transformasi Digitalisasi Pendidikan di SMA Swasta Dharma Karya Beringin Deli Serdang Melalui Peningkatan Pembelajaran Digital dan Pengembangan Non-Akademik Siswa - Sinaga, Nenni Triana; Verentia, Cleydia Lisyeni; Sitanggang, Brian Arswendy; Siahaan, Immanuel Natanael; Manurung, Anjeli Artha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Digitization has become a crucial factor in shaping the educational landscape. This transformation offers opportunities to enhance digital learning and foster student development beyond academics. This community service explores the role of digital transformation in education at SMA Swasta Dharma Karya, focusing on improving digital learning methods and nurturing non-academic aspects among students. Through a comprehensive approach involving observation, documentation, and in-depth interviews, the implementation of digital programs and their impact on the teaching and learning process are examined. Findings from this study reveal significant benefits of integrating digital technology into education, such as a shift towards more interactive and engaging learning environments and an emphasis on holistic student development beyond academic achievements. These improvements not only enhance the quality of education but also prepare students for the challenges of the digital era, ultimately contributing to their overall growth and success